2019
DOI: 10.1016/j.sleep.2019.11.302
|View full text |Cite
|
Sign up to set email alerts
|

Placental oxygen transfer reduces hypoxia/reoxygenation swings in fetal blood in a sheep model of gestational sleep apnea

Abstract: AIM: Obstructive sleep apnea (OSA), characterized by events of hypoxiareoxygenation, is highly prevalent in pregnancy, negatively affecting the gestation process and particularly the fetus. Whether the consequences of OSA on the fetus and offspring are mainly caused by systemic alterations in the mother or by direct effect of intermittent hypoxia in the fetus is unknown. In fact, how apnea-induced hypoxemic swings in OSA are transmitted across the placenta remains to be investigated. The aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…The association between maternal anemia and higher UV O 2 content is biologically plausible and may in fact be attributed to an adaptive mechanism in pregnancy physiology that causes easier unloading of O 2 to the fetus. This hypothesis has been demonstrated by Paulone et al 24 26,27 In fact, the rate of O 2 consumption during pregnancy increases up to 20% compared with nonpregnant individuals to accommodate the O 2 demands of the placenta and fetus. 28 Compensatory adaptations in placental physiology may also play a role.…”
Section: Discussionmentioning
confidence: 74%
“…The association between maternal anemia and higher UV O 2 content is biologically plausible and may in fact be attributed to an adaptive mechanism in pregnancy physiology that causes easier unloading of O 2 to the fetus. This hypothesis has been demonstrated by Paulone et al 24 26,27 In fact, the rate of O 2 consumption during pregnancy increases up to 20% compared with nonpregnant individuals to accommodate the O 2 demands of the placenta and fetus. 28 Compensatory adaptations in placental physiology may also play a role.…”
Section: Discussionmentioning
confidence: 74%
“…Other interesting study showed how intermittent hypoxia are transmitted to the fetus in a sleep apnoea ewe model. ALMENDROS et al [39] subjected pregnant ewes to intermittent hypoxia and measured oxygen partial pressure simultaneously on the femoral artery of the mother and in the umbilical vein. Finally, the work from OP DE BEECK et al [40] showed that higher loop gain is associated with a reduced upper airway stimulation.…”
Section: Insights Into the Pathophysiology Of Sdbmentioning
confidence: 99%
“…A lmendros et al . [ 39 ] subjected pregnant ewes to intermittent hypoxia and measured oxygen partial pressure simultaneously on the femoral artery of the mother and in the umbilical vein. Finally, the work from O p de B eeck et al .…”
Section: Insights Into the Pathophysiology Of Sdbmentioning
confidence: 99%
“…As cores representam: preto, normoxia aérea e aquática (bursa cloacal); verde, anóxia aérea e normoxia aquática; amarelo, anoxia aérea e aquática, (bursa cloacal); azul, anoxia aérea e hiperóxia aquática (bursa cloacal) e; vermelho, anoxia aérea e hiperóxia aquática (cavidade bucofaringeal) . Fonte: Cordeiro, 2019 (FORMENTI et al, 2015;ALMENDROS et al, 2019).…”
Section: Análises Estatísticasunclassified